The concept of the extension of the railway overpass in the central part of WWK - Maciej Kruszyna; Jacek Makuch (Przegląd Komunikacyjny)
Abstract: The Wrocław Railway Node (WWK) was briefly characterized in the introduction to the paper. The attention to the need to increase the level of rail use in servicing city traffic in Wrocław was drawn too. Reference was made to the original proposals of the agglomeration railway system for Wrocław. The scope of necessary investment and non-investment activities was analyzed in order to increase the capacity of the cross-city railway route and the adjacent routes. It was proposed to build the fourth track on the south side of the overpass of Wrocław railway diameter and new stops "Świdnicka" and "Grabiszyńska". In the conclusion, the need to create a second railway tunnel diameter in the longer term was signaled. Keywords: Agglomeration railway; Cross-city route; Railway overpass; WWK (Wrocław Railway Node)